1997
DOI: 10.1007/bf02442915
|View full text |Cite
|
Sign up to set email alerts
|

The PPGMRPP repetitive epitope of the Sm autoantigen: Antigenic specificity induced by conformational changes. Application of the Sequential Oligopeptide Carriers (SOCs)

Abstract: SUMMARYThe PPGMRPP sequence, found in several copies in the Sm and U1RNP autoantigens, is the main target of antiSm and anti-U1RNP antibodies in systemic lupus erythematosus (SLE) and mixed connective tissue disease (MCTD) patient's sera. It is also recognized, to a lower extent, by anti-Ro/SSA and anti-LaJSSB specificities. The PPGMRPP-NH2 peptide amide and the PPGMRPP peptide, which is bound to a pentameric sequential oligopeptide carrier (SOC5), were examined by 1H-NMR spectroscopy and ELISA assays, using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…These prerequisites were fulfilled in the present study: Aminoacid analysis of the purified (PPGMRPP) 5 -SOC 5 gave aminoacid molarities as expected; the 1 H-NMR spectra confirmed further the purity of our material [25] as well as that the PPGM-RPP epitope exists on SOC in a unique conformation. Therefore it was not surprising that immunization of animals with the immunogen (PPGMRPP) 5 -SOC 5 elicited an immune response specific for the PPGM-RPP epitope, rather than spreading to other epitopes of the spliceosome.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These prerequisites were fulfilled in the present study: Aminoacid analysis of the purified (PPGMRPP) 5 -SOC 5 gave aminoacid molarities as expected; the 1 H-NMR spectra confirmed further the purity of our material [25] as well as that the PPGM-RPP epitope exists on SOC in a unique conformation. Therefore it was not surprising that immunization of animals with the immunogen (PPGMRPP) 5 -SOC 5 elicited an immune response specific for the PPGM-RPP epitope, rather than spreading to other epitopes of the spliceosome.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, we have observed by NMR experiments three conformers of the PPGMRPP epitope in solution, which are structurally [15] different from each other and show various cross reactivities. However, only one of these conformers predominates when the PPGMRPP peptide is anchored to SOCs [25].…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the occurrence of these multiple conformers may explain why the PPGMRPP epitope is recognized by autoantibody species other (antiRo/La) than anti-Sm and anti-U1RNP [123]. However, the prevalence of one conformer of PPGMRPP after anchorage to SOC 5 -I, as demonstrated by 1 H-NMR analysis, resulted in a complete loss of the unrelated reactivity (anti-Ro/La) and an almost quantitative recognition by anti-Sm autoantibodies [103,124]. Fig.…”
Section: Conformational Analysis Of the Soc N -Conjugatesmentioning
confidence: 89%
“…Taking advantage of the plethora of amino-protective groups and by applying an orthogonal protection strategy, it was feasible to shape SOC n -conjugates Ac-Aib-Lys-Aib-Gly-Aib-Lys-Aib-Gly-Aib-Lys-Aib-Gly Peptide Peptide Peptide with identical or alternate ABAB motifs, where A and B represent different epitopes, as for example two types of B cell epitopes, B and T cell epitopes or CD4+ and CD8+ T cell epitopes. Two N-protective groups, Boc-and Fmoc-, are required for the attachment of identical copies of epitopes to the Lys-N ε H 2 groups of the carrier on the Pam resin [96,103], whereas an orthogonal system with three N-protective groups as Boc-, Fmoc-, and Alloc-(Pam resin) or Fmoc-, Alloc-and Mtt-(Wang resin) is needed for grafting two different epitopes to the carrier (Fig. 7) [104,105].…”
Section: Synthetic Aspects Purification and Characterizationmentioning
confidence: 99%
“…It also appeared, in other studies, that conformation greatly guided the recognition process, as demonstrated by the fact that the amide form converted from the C-terminal carboxylate group of the parent peptide reduced anti-Ro/La recognition. 47,48 Bianco et al described a fulleropeptide 27 ( Figure 6C) which derived from the nucleosomal histone (H3) protein attached to a L-fulleropyrrolidino-glutamic acid residue. 49 Molecular modeling research suggested that this peptide analog conserved the same binding capacity to major histocompatibility complex molecules as the parent peptide; however, further studies are required to verify whether it stimulates or inhibits T-cell responses.…”
mentioning
confidence: 99%